Dimension index method for climate change vulnerability assessment - Duong, Hong Son (ĐHQGHN, 2017)
Vulnerability assessment plays a key role on mitigation and adaptation to climate change. It can be a tool for managers and policy makers to define the area or sector which is the most sensitive to climate change in order to make appropriate policy and management decisions. Vulnerability is defined as a function of 3 components: exposure, sensitivity and adaptive capacity. As such, a method which can synchronizethe dimension of these 3 components is required to formulate the vulnerability level. This article describes a dimension index method for climate change vulnerability assessment and the result of pilot application in agriculture sector in Ca Mau province, Vietnam.